A low-profile flexible planar monopole antenna for biomedical applications - Hossain, A K M Zakir; Islam, Md Shazzadul; Kayser Azam, S. M.; Ibrahimy, Muhammad I.; Motakabber, S.M.A. (Elsevier B.V., 2022)
This article proposes a low profile planar monopole antenna on flexible substrate. The antenna is designed with an elliptical slot inserted in a rectangular patch by utilizing the coplanar waveguide (CPW) feeding technique on a polyimide substrate. The proposed antenna operates within 7–14 GHz (S11 < -10 dB) with a minimum return loss is observed as low as – 58 dB by simulation, whereas the entire X-band is covered by the – 20 dB bandwidth while maintaining an excellent VSWR of almost 1. Also, the antenna exhibits an average gain of 4 dBi while the average radiation efficiency is 92%. The maximum SAR of the proposed antenna for 1 g mass is below 1.0 W/Kg throughout the entire bandwidth. To observe flexibility, four different bending conditions of the antenna have been analyzed. For experimentation, the antenna has been realized as a prototype by using a low-cost fabrication process. The measurement reveals that the prototype has a 10 dB bandwidth of 5.4 GHz. During In-Vivo test, over the variation of 0 -3 mm distance between the antenna-prototype and the human chest/chicken breast tissue, the best performance is obtained at 3 mm in terms of the return loss. One of the significant featuresof the proposed design is its measured average and peak gain of 4.4 dBi and of 6.33 dBi respectively with a measured average efficiency of 65%. The proposed antenna has a compact size of 13 x 13 mm2 (0:35kg - 0:35kg), and its performance remains nominally constant even under different bending conditions which makes the antenna suitable for biomedical imaging applications. A new figure-of-merit has been introduced to evaluate the overall performance based on different antenna key parameters. The fabricated antenna would contribute to the future biomedical research by utilizing X-band frequencies.